Entrepreneurship Intentions of Public Universities in Turkey: Going Beyond Education and Research? - AŞKUN, OLCAY BİGE (ELSEVIER SCIENCE BV, 2012)
Today, universities play a fundamental role in establishing and developing an entrepreneurship-oriented economy as they represent the main source of new knowledge. Roles of universities in economic growth have evolved in time and grew beyond their traditional teaching and research tasks. Universities are anymore expected to introduce solutions to social and industrial needs by exploiting the knowledge that is created by research. Universities even strategically aim to create wealth by investing in business, by building linkages, partnerships with technological enterprises or by creating new firms through academic entrepreneurship. Evolution of roles of universities in economic growth received close attention of scholars and found place in multiple disciplines like business management and economics literature and research for decades in developed countries. However there is still a significant need for research about the entrepreneurial intentions, activities and contributions of universities to economic growth in developing countries. Findings of this sort of studies can be very helpful to policy makers of these countries in academy, industry and government for utilizing entrepreneurship for economic growth, employment and increasing welfare of their people. In this context, study aims to determine the entrepreneurial intentions of public universities in Turkey by exploring their strategic postures, cultural and organizational units that supplement and support entrepreneurial activities and collaborations. Major characteristics of universities that determine their entrepreneurial intentions are derived from theoretical background. By conducting a qualitative content analysis, these characteristics are searched through Web sites of public universities in Turkey in academic year of 2011-2012. Findings regarding entrepreneurial intentions of universities that are reflected in their strategies, culture, institutional infrastructure, collaborations/partnerships can provide evidence about not only current but also potential entrepreneurial behaviors of public universities in Turkey. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 8th International Strategic Management Conference
Keywords: Entrepreneurship; Higher Education Institutions; Entrepreneurship Education; Academic Entrepreneurship; ACADEMIC ENTREPRENEURSHIP; INNOVATION